Hubungan Lama Kerja Perawat Dengan Kepatuhan Pengisian Surgical Safety Checklist di Instalasi Bedah Sentral - Maria Karolina Selano; Yohanes Hendy Kurniawan; Priyo Sambodo (Jurnal Kepemimpinan dan Manajemen Keperawatan, 2019)
The use of the Surgical Safety Checklist reduces mortality and surgical complication. Nurse obedience in documenting the surgical safety checklist is still low. It is showed that there is a lack of nurses awareness about the importance of surgical safety checklist in an operation. This research aims to know about the relationship between the years of service of the nurse and compliance with filling surgical safety checklist at Central Operating Theatre. Design of this study uses cross-sectional approach. Sampling technique uses total sampling technique, samples taken for study as many as 23 respondents who met the inclusion and exclusion criteria. The data are described in table form and a Fisher test was conducted with spss 21. The highest work period are they who have light of work ≥ 3 years as many as 15 respondent (65,2%) and respondents who have length of work < 3 years as many as 8 respondent (34,8%), for nurses obedience  18 respondents (78,3%) who did not complete the surgical safety checklist while 5 respondents (21,7%) complete the surgical safety checklist correctly. Fisher statistic test obtained p-value data is 0,586 > 0,05. There is no relationship between the years of service of the nurse and compliance with filling surgical safety checklist at Central Operating Theatre